Molecular mechanisms of recurrent acute obstructive bronchitis in infants - Abaturov A.E.; Rusakova E.A. (Medičnì Perspektivi)
The article discusses the clinical and immunological features and mechanisms of recurrent acute obstructive bronchitis in infants. We have examined 102 children aged from 6 months to 3 years with acute obstructive bronchitis and signs of respiratory insufficiency of the I-II degree. There were 28 children with recurrent acute obstructive bronchitis and 74 patients with acute obstructive bronchitis,developed for the first time. We determined the concentration of total IgE, content of IFN-і, IL-4, IL-12 and IL-13 in serum by ELISA and the expression of the transcription factor NF-єB in lymphocytes of peripheral blood by flow cytometry in all the children. High level of IL-12 as compared to physiological norms in the dynamics of the disease was the characteristic feature of the children of both groups. And it was the factor, which detected a voltage of cell-mediated immune response and inflammation. The second specific feature was the high concentration of IgE. It was shown that the transcription factor NF-єB determined the cytokine status at the beginning of the disease, and in the period of convalescence. That fact did not depend on the number of previous acute obstructive bronchitis. However, there were violations of the mechanisms of NF-єB-associated signaling pathways activation, which manifested itself in an advantageous enhancement of the chains, determining the production of Th2-associated cytokines in children with recurrent acute obstructive bronchitis.